Best Approximation in Modular Spaces By Type of Nonexpansive Maps - Mohammed, Nadia Jasim; Abed, Salwa Salman (Iraqi Journal of Science, 2018)
This paper presents results about the existence of best approximations via nonexpansive type maps defined on modular spaces.